Crotoxin Inhibits Endothelial Cell Functions in Two- and Three-dimensional Tumor Microenvironment - Kato, Ellen Emi; Pimenta, Luciana Araújo; Almeida, Maíra Estanislau Soares de; Zambelli, Vanessa Olzon; Santos, Marinilce Fagundes dos; Sampaio, Sandra Coccuzzo (Frontiers in Pharmacology, 2021)
Antitumor property of Crotoxin (CTX), the major toxin from Crotalus durissus terrificus snake venom, has been demonstrated in experimental animal models and clinical trials. However, the direct action of this toxin on the significant events involved in neovascularization, which are essential for tumor growth and survival, has not been confirmed. This study investigated the effects of CTX on the key parameters of neovascularization in two- and three-dimensional culture models. Murine endothelial cell lines derived from thymus hemangioma (t.End.1) were treated at different concentrations of CTX (6.25 nM to 200 nM). Endothelial cell proliferation, cell adhesion, and actin cytoskeletal dynamics on laminin (10 µg/mL), type I collagen (10 µg/mL), and fibronectin (3 µg/mL) were evaluated along with the endothelial cell migration and formation of capillary-like tubes in 3D Matrigel. CTX concentration of 50 nM inhibited tube formation on 3D Matrigel and impaired cell adhesion, proliferation, and migration under both culture medium and tumor-conditioned medium. These actions were not accountable for the loss of cell viability. Inhibition of cell adhesion to different extracellular matrix components was related to the reduction of αv and α2 integrin distribution and cytoskeletal actin polymerization (F-actin), accompanied by inhibition of focal adhesion kinase (FAK), Rac1 (GTPase) signaling proteins, and actin-related protein 2/3 (Arp 2/3) complex. This study proved that CTX inhibits the major events involved in angiogenesis, particularly against tumor stimuli, highlighting the importance of the anti-angiogenic action of CTX in inhibition of tumor progression.